2007
DOI: 10.1038/ismej.2007.54
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pyogenes serotype-dependent and independent changes in infected HEp-2 epithelial cells

Abstract: The adherence, internalization and persistence of the human pathogen Streptococcus pyogenes (group A streptococci, GAS) to and within host cells were studied, and the induced responses of the infected epithelial cells were investigated. Next to common cellular responses on GAS infection, many responses of the infected HEp-2 epithelial cells are GAS serotype-specific. Moreover, several cellular responses do not correlate with the actual bacterial numbers adherent, internalized and persistent within the cells or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…5). The overall rate of internalization was low but was consistent with previously published reports for M1 serotype strains (30). As with PMNs, cytotoxicity was monitored by assessing the amount of lactate dehydrogenase released from infected cells.…”
Section: Rt-pcr (Qrt-pcr) Did Reveal Differences In Transcription Ofsupporting
confidence: 66%
See 2 more Smart Citations
“…5). The overall rate of internalization was low but was consistent with previously published reports for M1 serotype strains (30). As with PMNs, cytotoxicity was monitored by assessing the amount of lactate dehydrogenase released from infected cells.…”
Section: Rt-pcr (Qrt-pcr) Did Reveal Differences In Transcription Ofsupporting
confidence: 66%
“…It has been demonstrated that GAS can enter epithelial cells (24,30,34,38,42,54), so we investigated whether or not SpyA affects bacterial entry into epithelial monolayers in vitro. HeLa cells were infected with wild-type or spyA mutant bacteria at a multiplicity of infection (MOI) of ϳ10:1, and association and internalization into these cells was measured.…”
Section: Rt-pcr (Qrt-pcr) Did Reveal Differences In Transcription Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several decades, the molecular mechanisms underlying the adherence and internalization of GAS to epithelial cells as well as their intricate interactions have been extensively studied (8 -12). Although it was considered that most internalized GAS organisms are eliminated by intracellular killing, massive internalization or adherence of GAS preferentially induces programmed cell death of epithelial cells (13)(14)(15). These processes may lead to exposure of underlying tissues or cause damage to epithelium, providing GAS with a route to deeper tissues (intracellular route).…”
mentioning
confidence: 99%
“…Whereas intracellular killing eliminates most internalized GAS pathogens, apoptosis of epithelial cells is preferentially induced by massive internalization or bacterial adherence of GAS [18][19][20]. In response to bacterial infections, apoptotic cell death can remove infected and damaged cells, thereby protecting the underlying tissues from bacterial replication and dissemination.…”
Section: Invasion Via Intracellular Routementioning
confidence: 99%